Demographic considerations of African (Black) schizophrenic patients presenting at Baragwanth hospital psychiatry outpatients and inpatients facilities - Brauteseth, Leif Trygvar (My University, 2016)
A paucity of published data was encountered when investigating the demography of most psychiatric problems occurring in the in black South African population. Even less demographic data was available which pertains specifically to black Schizophrenic patients and no published data Was found which was specific to Schizophrenia amongst Baragwanath Hospi- tal Psychiatry patients. It was intended that the stUdy would firstly identify this group of patients and determine whether compliance and/or relapse was related to any particular demographic factors, and secondly to recommend possible ways of catering more effectively for the mental health care needs of this group of patients. A descriptive demographic study was conducted using a questionnaire survey for data collection. A sample of 104 patients who fulfiiled the DSM III-R criteria for schizophrenia was studied. Statistically significant differences between male and female patients were noted for some demographic variables. Factor such as education, socioeconomic status, social support systems, medical management /follow-up systems and substance abuse patterns Were examined. Difficulties encountered in conducting the study were discussed. The main limitation of the study was that the findings were not generalizable beyond the study population.
A Research Report Submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in partial fulfilment of the Degree of Master of Medicine in Psychiatry. Johanrlesburg October 1992